2022
DOI: 10.1111/coa.14006
|View full text |Cite
|
Sign up to set email alerts
|

Safety of day‐case endoscopic sinus surgery in England: An observational study using an administrative dataset

Abstract: Introduction: As elective surgical services recover from the COVID-19 pandemic a movement towards day-case surgery may reduce waiting lists. However, evidence is needed to show that day-case surgery is safe for endoscopic sinus surgery (ESS). The aim of this study was to investigate the safety of day-case ESS in England.Design: Secondary analysis of administrative data.Methods: We extracted data from the Hospital Episodes Statistics database for the 5 years from 1 April 2014 to 31 March 2019. Patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Day-case surgery should be the default model for low complexity procedures and be offered to all patients unless there is a clear contraindication. There is substantial unwarranted variation in day-case rates across NHS hospital Trusts in England, despite evidence that day-case surgery is safe for carefully selected patients [15][16][17][18]. Recent modelling performed by the GIRFT programme and Greener NHS found that progressive increases in the rates of day-case surgery performed for transurethral resection of bladder tumour (TURBT) surgery has saved 20.9 million kgCO 2 e over 9 years (2013/2014 to 2021/2022), and further adoption of day-case surgery could reduce carbon emissions by a further 217,599 kgCO 2 e (based on 2021/ 2022 data [19]).…”
Section: Day-case Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Day-case surgery should be the default model for low complexity procedures and be offered to all patients unless there is a clear contraindication. There is substantial unwarranted variation in day-case rates across NHS hospital Trusts in England, despite evidence that day-case surgery is safe for carefully selected patients [15][16][17][18]. Recent modelling performed by the GIRFT programme and Greener NHS found that progressive increases in the rates of day-case surgery performed for transurethral resection of bladder tumour (TURBT) surgery has saved 20.9 million kgCO 2 e over 9 years (2013/2014 to 2021/2022), and further adoption of day-case surgery could reduce carbon emissions by a further 217,599 kgCO 2 e (based on 2021/ 2022 data [19]).…”
Section: Day-case Surgerymentioning
confidence: 99%
“…These included a reluctance to change current practice; lack of day‐case infrastructure; concern that outcomes would be compromised; and belief that day‐case rates were already ‘optimal’. Despite clear progress at a national level with recent increases in rates of day‐case surgery across a range of procedures and specialties [15–18], rates vary considerably by Trust, hospital and surgical specialty. In addition, rates of conversion from day‐case to inpatient stay vary from 3% to 39% across Trusts in England [13].…”
Section: Barriers To Change and Facilitators Of Improvementmentioning
confidence: 99%
“…No superiority of in-patient stay was demonstrated in terms of patient outcomes or readmission rates. 12 Operating theatre CO 2 equivalent emissions…”
Section: Carbon Footprint Of Long Patient Staymentioning
confidence: 99%